1991
DOI: 10.1177/014920639101700406
|View full text |Cite
|
Sign up to set email alerts
|

Development of Organizational Commitment During the First Year of Employment: A Longitudinal Study of Pre- and Post-Entry Influences

Abstract: To test hypotheses concerning the influence of prospective and retro-spective rationality in the development of organizational commitment, we measured both the affective and continuance commitment of recent university graduates on three occasions during theirfirst year of employment and examined their relations with variables measured prior to and following entry into an organization. Prior to entry, we measured variables presumed to bind individuals to their choice of organization (i.e., volition, irrevocabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 34 publications
4
118
0
9
Order By: Relevance
“…Cole and Johnson (2007) and Meyer et al (1991) described AC as an emotional attachment to the organization. AC refers to employees' involvement in, emotional attachment to, and identification with the organization (Meyer and Allen, 1988).…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cole and Johnson (2007) and Meyer et al (1991) described AC as an emotional attachment to the organization. AC refers to employees' involvement in, emotional attachment to, and identification with the organization (Meyer and Allen, 1988).…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
“…Allen and Meyer (1996) defined CC as the degree which an employee needs to continue working with an organization since the expense of leaving is too high. Meyer et al (1991) they found it difficult to find alternative job, so they prefer to continue their work to increase their commitment.…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
“…Employee commitment can be reinforced by organizational policies that support accurate descriptions of job responsibilities, and flexibility in not only working conditions but also through choices and policies (Meyer, Bobocel & Allen 1991). Work-family policies and employee control over time, flexibility and pace of work were also found to support employee commitment (Golembiewski, et al 1974;Eaton 2003).…”
Section: Commitmentmentioning
confidence: 96%
“…The investigations presented within provide definitions of organizational commitment as well as measures of commitment (Allen & Meyer 1990b;Buchanan, 1974;Meyer & Allen, 1991;Mowday, Steers, & Porter, 1979;O'Reilly & Chatman, 1986). The researchers use samples composed of paid (Anderson, Martin, & Riddle, 2001;Finegan, 2000) and unpaid (Cuskelly & Boag 2001;Cuskelly, McIntyre, & Boag, 1998;Dailey, 1984) organization members to determine relationships between organizational commitment and other valued organizational outcomes.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Using the OCQ to measure unpaid staff member organizational commitment, Cuskelly et aI., (1998) Researchers (Allen & Meyer, 1990b;Buchanan, 1974;Meyer & Allen, 1991;Mowday et aI., 1979;O'Reilly & Chatman, 1986) have developed single dimension and multi-dimension measures of organizational commitment. From these measures, we have discovered processes facilitating organizational commitment vary upon stage of organization membership (Buchanan, 1974).…”
Section: Unpaid Organization Members and Organizational Commitmentmentioning
confidence: 99%